The role of small GTPases in Alzheimer’s disease tau pathologies - Hoegy, Peter; Chen, Yan-Hua; Lu, Qun (Frontiers in Cellular Neuroscience, 2025)
Microtubule-associated protein (MAP) tau stabilizes neuronal microtubules in axonal transport and contributes to healthy synapses. In Alzheimer’s disease (AD), tau proteins become hyperphosphorylated, reduce microtubule binding, and aggregate into paired helical filaments (PHFs) in neurofibrillary tangles (NFTs). Although the steps of this dysregulation of tau are well established, the mechanisms by which each step is regulated remain incompletely understood. Misfolded protein aggregates, such as amyloid β-peptides (Aβ), are degraded by autophagy and lysosomal pathways, in which small GTPases play essential roles. However, how tau aggregates and spreads from nerve cells and whether small GTPases similarly play pivotal roles are not as clear. Here we review the recent evidence to propose that small GTPases are important in tau protein posttranslational phosphorylation, aggregation, and clearance. As such, small GTPases may prove to be important therapeutic targets that can reduce the AD tau burden.